Analisis Pengaruh Harga Emas dan Minyak Mentah Periode Terhadap LQ45 Menggunakan Model ARDL - Yulia Putri Tio; Rosmiati Kristin; Didik Gunawan; Willy Cahyadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of gold and crude oil prices on LQ45 using the ARDL approach. In the research carried out, researchers used the variables Gold Price and Oil Price. The data used is secondary data sourced from the websites www.yahoo.co.id and investing.com. Using purposive sampling technique and the research sample obtained was 240 time series data. The results of this research show that gold prices have a negative effect and crude oil prices have a positive effect in the long term on LQ45. The results of this research can be a reference material for investors in developing investment strategies, especially during a crisis.